Platelet-rich concentrate in serum-free medium enhances cartilage-specific extracellular matrix synthesis and reduces chondrocyte hypertrophy of human mesenchymal stromal cells encapsulated in alginate. (2nd January 2019) - Samuel, Shani; Ahmad, Raja Elina; Ramasamy, Thamil Selvee; Karunanithi, Puvanan; Naveen, Sangeetha Vasudevaraj; Kamarul, Tunku
Abstract: Platelet-rich concentrate (PRC), used in conjunction with other chondroinductive growth factors, have been shown to induce chondrogenesis of human mesenchymal stromal cells (hMSC) in pellet culture. However, pellet culture systems promote cell hypertrophy and the presence of other chondroinductive growth factors in the culture media used in previous studies obscures accurate determination of the effect of platelet itself in inducing chondrogenic differentiation. Hence, this study aimed to investigate the effect of PRC alone in enhancing the chondrogenic differentiation potential of human mesenchymal stromal cells (hMSC) encapsulated in three-dimensional alginate constructs. Cells encapsulated in alginate were cultured in serum-free medium supplemented with only 15% PRC. Scanning electron microscopy was used to determine the cell morphology. Chondrogenic molecular signature of hMSCs was determined by quantitative real-time PCR and verified at protein levels via immunohistochemistry and enzyme-linked immunosorbent assay. Results showed that the cells cultured in the presence of PRC for 24 days maintained a chondrocytic phenotype and demonstrated minimal upregulation of cartilaginous extracellular matrix (ECM) marker genes ( SOX9, TNC, COL2, ACAN, COMP ) and reduced expression of chondrocyte hypertrophy genes ( Col X, Runx2 ) compared to the standard chondrogenic medium ( p  < 0.05). PRC group had correspondingly higher levels of glycosaminoglycan and increased concentration of chondrogenic specific proteins (COL2, ACAN, COMP) in the ECM. In conclusion, PRC alone appears to be very potent in inducing chondrogenic differentiation of hMSCs and offers additional benefit of suppressing chondrocyte hypertrophy, rendering it a promising approach for providing abundant pool of chondrogenic MSCs for application in cartilage tissue engineering.